Portfolios and Accreditation of Prior Experiential Learning (APEL) make credits... or problems? - Murray PJ (Nurse Education Today, 1994)
A selected literature review on the use of portfolios is presented and points in relation to their use, particularly within the English National Board (ENB) Framework and Higher Award, are discussed. Aspects such as the potentially time-consuming nature of portfolio production and the absence of research on their use in British nursing are highlighted. The author concludes by suggesting some aspects of portfolio use that might benefit from monitoring and research.